A REST Service for the Visualization of Clinical Time Series Data in the Context of Clinical Decision Support. - Unberath, Philipp; Prokosch, Hans-Ulrich; Kraus, Stefan (ICT for Health Science Research, 2019)
BACKGROUND: University Hospital Erlangen provides clinical decision support (CDS) functions in the intensive care setting, that are based on the Arden Syntax standard. These CDS functions generate extensive output, including patient data charts. In the course of the migration of our CDS platform we revised the charting tool because although the tool was generally perceived as useful, the clinical users reported several shortcomings. OBJECTIVE: During the migration of our CDS platform, we aimed at resolving the reported shortcomings and at developing a reusable and parameterizable charting tool, driven by best practices and requirements of local clinicians. METHODS: We conducted a requirements analysis with local clinicians and searched the literature for well-established guidelines for clinical charts. Using a charting library, we then implemented the tool based on the found criteria and provided it with a REST interface. RESULTS: The criteria catalog included 18 requirements, all of which were successfully implemented. The new charting tool fully replaced the previous implementation in clinical routine. It also provides a web interface that enables clinicians to configure charts without programming skills. CONCLUSION: The new charting tool combines local preferences with best practices for visualization of clinical time series data. With its REST interface and reusable design it can be easily integrated in existing CDS platforms.
EVALuna2:209494